The Impact of Structured Physical Activity Programs on Cognitive and Physical Health in Elderly Individuals with Neurodegenerative Disorders: A Comprehensive Review - Alotaibi, Mohammed Abdullah Shari; ALDAGHMANI, MEZNAH ALAQAN MOHAMMED; ALMADHI, EMAN ABDULRAHMAN NASSER; Alanezi, Mashael Saad; Hemili, Omrana Mussa Ali; Alosimi, Naif Awod; Alqahtani, Sultan Fahad; Algubawi, Mohammed Hathal; Aljaber, Amira Nasser; Alotebi, Ghazi Saud Marzoq (Journal of Ecohumanism, 2024)
Neurodegenerative illnesses provide considerable health concerns for the aged, leading to cognitive and motor deficits. Alzheimer’s disease and Parkinson’s disease are common in older persons, requiring appropriate treatment measures to improve their quality of life. Physical exercise has emerged as a viable non-pharmacological strategy that may alleviate the consequences of various illnesses. The influence of physical exercise programs on cognitive function, physical capabilities, and general well-being in older persons with neurodegenerative illnesses was comprehensively evaluated in this literature review. A thorough search was performed across many databases, including PubMed, Scopus, and Cochrane Library, concentrating on interventional studies that assessed the effectiveness of several exercise modalities, such as aerobic training, resistance exercises, and mind-body practices.The study revealed significant data demonstrating the efficacy of physical exercise in strengthening cognitive functioning, improving physical mobility, and increasing overall quality of life in older adults with neurodegenerative disorders. Consistent participation in organized exercise regimens was associated with enhanced neuroplasticity, augmented neurogenesis, and decreased inflammation, leading to superior cognitive results. Particular modalities, such as Tai Chi and strength training, have shown significant advantages in improving motor skills and balance, hence reducing the risk of falls. Physical exercise must be included as an essential element of care for elderly individuals with neurodegenerative diseases. Customized exercise regimens may markedly enhance cognitive and physical well-being, thereby improving overall quality of life. Future research needs to concentrate on longitudinal studies to determine appropriate exercise prescriptions and investigate novel delivery strategies to enhance adherence.